imulation Results of Single Stage AC- AC Converter for Induction Heating - S. ARUMUGAM (Analele Universităţii "Dunărea de Jos" Galaţi: Fascicula III, Electrotehnică, Electronică, Automatică, Informatică, 2010)
This paper presents simulation of single stage Induction heating system with series Load Resonance. Low frequency AC is converted in to High Frequency Ac using newly developed ZVS-PWM high frequency inverter. This High Frequency is used for Induction Heating .Single stage AC-AC converter system is modeled and simulated using Matlab Simulink. The simulation results of ZVS-PWM high frequency system are presented. The effectiveness of this UFAC-to-HFAC direct power frequency converter using IGBTs for consumer high-frequency IH appliances is evaluated and proved on the basis of simulation results.